INTERNAL DISEASE COURSE AS A BASIC ELEMENT OF SPECIALISTS TRAINING IN MEDICINE - N. A. Moukhin (Сеченовский вестник)
Role of internal disease course in modern medical educations and significance of physical examination skills are discussed